2020
DOI: 10.1016/j.jseint.2020.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for increased shoulder Cutibacterium acnes burden

Abstract: Background Cutibacterium acnes is the primary cause of shoulder surgery infections, but the predisposition to larger skin counts and potentially higher risk for postoperative infection remains unclear. This study aimed to quantify risk factors influencing endogenous C. acnes burden and to compare counts among 4 shoulder sites. Methods C. acnes counts were quantified via a detergent scrub technique for 173 particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
5
0
3
Order By: Relevance
“…This result might be attributed to ethnicity and incubation period for the detection of C. acnes. East or southeast Asians had the lowest detection rate of C. acnes compared with all other ethnicities [23]. The incubation period for organisms was routinely three days only in our institute, although a 13-14 day incubation period is essential for the detection of C. acnes [24].…”
Section: Discussionmentioning
confidence: 90%
“…This result might be attributed to ethnicity and incubation period for the detection of C. acnes. East or southeast Asians had the lowest detection rate of C. acnes compared with all other ethnicities [23]. The incubation period for organisms was routinely three days only in our institute, although a 13-14 day incubation period is essential for the detection of C. acnes [24].…”
Section: Discussionmentioning
confidence: 90%
“…The predominance of males in the findings of C. acnes has been previously reported by several studies. 2 3 14 15 Kaveeshwar et al 15 found a correlation between isolation of this agent and age lower than 40 years. The higher prevalence stake in males and young people are related to the more active production of the sebaceous glands in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence stake in males and young people are related to the more active production of the sebaceous glands in these individuals. 15 Finally, Nagaya et al 16 showed that patients with an anesthetic risk score higher than ASA III had a higher risk of developing infection after shoulder arthroplasty. Interestingly, in our study we found a higher correlation of microorganism isolation in ASA I patients, with a tendency to isolate C. acnes .…”
Section: Discussionmentioning
confidence: 99%
“…Pre-measurements of the patient´s immunological, microbial and cellular status would provide insights into the patient's susceptibility to infection. The choice of antibiotic Previous surgeries and preoperative corticosteroid injections- [8,18] Reverse total shoulder arthroplasty relative to total shoulder arthroplasty- [17] Long surgery duration or traumatic arthroplasties- [16] Limited antibiotic prophylaxis control of C. acnes- [17,60] Low penetration in deeper skin of pre-operational disinfection- [60,58] administered as prophylaxis should be based on the above measurements and a clinical evaluation of the patient. Implementing selective and personalized pre-operative skin preparationsdecided based on the patient's health, lifestyle, age, and sex and their individual immunological-microbial statuscould further minimize the likelihood of post-operative infections.…”
Section: Surgical Site Infectionsmentioning
confidence: 99%
“…Cutibacterium acnes is part of the healthy skin microbiome, inhabits the pilosebaceous units in the deep skin and thus often evades pre-operative disinfection [59][60][61]. With a surgical incision, C. acnes gains access to deeper skin layers and soft tissue [62].…”
Section: Cutibacterium Acnesmentioning
confidence: 99%